Measurement of the CP violating phase βs in B0s → J/ψφ decays - Oakes, L (2010)
The CP violating phase βJ/ψφs is measured in decays of B0s → J/ψφ. This measurement uses 5.2 fb-1 of data collected in √—s = 1.96 TeV p̅p collisions at the Fermilab Tevatron with the CDF Run-II detector. CP violation in the B0s-̅B0sbar system is predicted to be very small in the Standard Model. However, several theories beyond the Standard Model allow enhancements to this quantity by heavier, New Physics particles entering second order weak mixing box diagrams. Previous measurements have hinted at a deviation from the Standard Model expectation value for βJ/ψφs with a significance of approximately 2σ. The measurement described in this thesis uses the highest statistics sample available to date in the B0s rightarrow; J/ψφ decay channel, where J/ψ → μ+ μ− and φ → K+K−. Furthermore, it contains several improvements over previous analyses, such as enhanced signal selection, fully calibrated particle ID and flavour tagging, and the inclusion of an additional decay component in the likelihood function. The added decay component considers S-wave states of KK pairs in the B0s → J/ψK+K− channel. The results are presented as 2-dimensional frequentist confidence regions for βJ/ψφs and ΔΓ (the width difference between the B0s mass eigenstates), and as a confidence interval for βJ/ψφs of [0.02,0.52] Ｕ [1.08, 1.55] at the 68 % confidence level. The measurement of the CP violating phase obtained in this thesis is complemented by the world's most precise measurement of the lifetime τs = 1.53 ± 0.025 (stat.) ± 0.012 (syst.) ps and decay width difference ΔΓ = 0.075 ± 0 .035 (stat.) ± 0.01 (syst.) ps−1 of the B0s meson, with the assumption of no CP violation.